Peningkatan Keterampilan Menulis Teks Deskriptif dengan Menggunakan Media Pembelajaran Berbasis Audio Visual pada Siswa Kelas VII UPTD SMPN 4 Kecamatan Guguak - Meta Agustina (LPPI Yayasan Almahmudi bin Dahlan, 2023)
In modern life, students' mastery of written language is very necessary. The reality in the field of writing learning in schools is inadequate due to one of the reasons being the delivery of material which still uses monotonous media. The aim of this research is to improve descriptive text writing skills using audio-visual learning media for Class VII UPTD students at SMPN 4, Guguak District. The method used in this research is Action Research which consists of 2 (two) cycles, and each cycle consists of: Planning, Implementation, Observation and reflection. Based on the results of action research, learning to write descriptive texts using audio-visual learning media can improve the descriptive text writing skills of students in Class VII UPTD SMPN 4 Guguak District. The results of the research show that the writing ability of class VII UPTD SMPN 4 students in Guguak sub-district at the beginning after applying audio-visual learning media in English lessons obtained a KM of 50%. In cycle 1 the KM was 71.4%, and in cycle II the highest score was 100%. Audio-visual learning media in student learning focuses more on the process until students discover the concept, which allows students to investigate for themselves various things which are then useful for students' intellectual and mental development. Keywords: Text Writing Ability, Learning Media, Audio Visual